Outbreak of aggressions and transmission of rabies in human beings by vampire bats in northeastern Brazil - Gonçalves,Marcio A.S. (2002)
Outbreaks of attacks upon human beings by vampire bats seems to be a common phenomenon in several regions of Latin America, but the occurrence of rabies infection among humans bled by vampires, is relatively low. In the present study, two outbreaks of human rabies transmitted by common vampire bats (Desmodus rotundus) are described from Bahia State, Northeasthern Brazil, in 1991 and 1992. The first was recorded in Aporá where 308 people were bled by vampire bats and three of these die from this zoonosis. The 2nd outbreak occurred in Conde where only five people were bled by vampires, and two deaths by rabies were registered. Our data suggest that rabies transmitted by bats basically depends on the presence of virus in the vampire bat population and not on the number of humans bled by them.